Frequency importance for sentence recognition in co-located noise, co-located speech, and spatially separated speech - Bosen, Adam K.; Wasiuk, Peter A.; Calandruccio, Lauren; Buss, Emily (The Journal of the Acoustical Society of America, 2024)
Frequency importance functions quantify the contribution of spectral frequencies to perception. Frequency importance has been well-characterized for speech recognition in quiet and steady-state noise. However, it is currently unknown whether frequency importance estimates generalize to more complex conditions such as listening in a multi-talker masker or when targets and maskers are spatially separated. Here, frequency importance was estimated by quantifying associations between local target-to-masker ratios at the output of an auditory filterbank and keyword recognition accuracy for sentences. Unlike traditional methods used to measure frequency importance, this technique estimates frequency importance without modifying the acoustic properties of the target or masker. Frequency importance was compared across sentences in noise and a two-talker masker, as well as sentences in a two-talker masker that was either co-located with or spatially separated from the target. Results indicate that frequency importance depends on masker type and spatial configuration. Frequencies above 5 kHz had lower importance and frequencies between 600 and 1900 Hz had higher importance in the presence of a two-talker masker relative to a noise masker. Spatial separation increased the importance of frequencies between 600 Hz and 5 kHz. Thus, frequency importance functions vary across listening conditions.
Keywords: dept.cmd; peer-reviewed

La rana or el rana: dual language learners' grammatical variability in narrative retells - Gusewski, Svenja; Rojas, Raúl (Language, Speech, and Hearing Services in Schools, 2024)
Purpose: This longitudinal study investigated the trajectory of Spanish article accuracy in Spanish–English dual language learners (DLLs) from preschool to first grade, addressing the need for longitudinal data on the variability of Spanish grammatical skills in DLLs in English immersion classrooms. Method: Language sample analysis was conducted on 336 Spanish and English narrative retells elicited from 31 Spanish–English DLLs (range: 45–85 months). Growth curve models captured within- and between-individual change in article accuracy from the beginning of preschool to the end of first grade. Results: As a group, DLLs did not exhibit significant positive or negative growth in Spanish article accuracy over time. On average, article accuracy remained stable at 76% from preschool throughout first grade. Participants exhibited significant variability in article accuracy that was partly explained by changes in Spanish proficiency. Spanish article accuracy was lower for DLLs with lower Spanish proficiency indexed by measures from the Spanish language samples, while English proficiency indexed by the English language samples did not affect Spanish article accuracy. Conclusions: These findings suggest that expectations for Spanish grammatical performance in DLLs need to be adjusted to account for the possible impact of not receiving Spanish support in English immersion school settings. DLLs in these instructional programs do not exhibit article accuracy at a level expected for monolingual Spanish speakers. Significant individual differences in both individual status and growth rates of Spanish article accuracy highlight the broad variability in Spanish language skills of DLLs in the United States.
Keywords: dept.cmd; peer-reviewed

Speech-Language Pathologists' Use of Side-Lying Position in Infant Modified Barium Swallow Studies: A Qualitative Investigation - Smith, Julian Bergen; O, 'Donoghue Cynthia; Jones, Rebecca (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: This qualitative study explored the practices of hospital-based speech-language pathologists (SLPs) conducting modified barium swallow studies (MBS) for infants at risk for dysphagia. Specifically, this research aimed to determine whether or not SLPs use side-lying position during MBS, to examine possible differences in the use of positioning, and to better understand SLPs' perceptions and experiences in this practice. Using a constructivist view, research questions guiding this inquiry were as follows: What is the current practice of hospital-based pediatric SLPs in regard to the use of side-lying position during infant MBS? What is the experience of the hospital-based SLP in their use of side-lying position during MBS? How do SLPs report perceived barriers or benefits to using side-lying position during MBS? Method: Employing a purposive-convenience sampling technique, data were collected using semistructured interviews of SLPs serving at-risk infants with dysphagia. All participants were practicing in Level-III or -IV neonatal intensive care units. Interviews were recorded, transcribed, loaded into NVivo, and coded using initial and consensus coding. Themes achieved saturation following six interviews. Results: Three themes emerged from the analysis: (a) variations in practice patterns, (b) factors influencing clinical practice, and (c) items that SLPs identified as needs to facilitate change in their clinical practice. Conclusions: Although SLPs acknowledged the importance of MBS replicating an infant's typical feeding, some SLPs who consistently use side-lying position during feeding do not assess feeding in side-lying position during MBS. This inconsistency in practice results from SLPs' perceived barriers, including lack of experience, concern over interdisciplinary conflict, need for MBS protocols, and lack of research on the potential impacts of side-lying positioning on swallowing. Participants reported the need for research to determine whether side-lying position alters, possibly improves, swallow functions and safety (e.g., airway protection) for at-risk infants.
Keywords: dept.cmd; peer-reviewed

Generalization in aphasia treatment: a tutorial for speech-language pathologists - Mayer, Jamie F.; Madden, Elizabeth B.; Mozeiko, Jennifer; Murray, Laura L.; Patterson, Janet P.; Purdy, Mary; Sandberg, Chaleece W.; Wallace, Sarah E. (American Journal of Speech-Language Pathology, 2024)
Purpose: Generalization has been defined and instantiated in a variety of ways over the last half-century, and this lack of consistency has created challenges for speech-language pathologists to plan for, implement, and measure generalization in aphasia treatment protocols. This tutorial provides an overview of generalization with a focus on how it relates to aphasia intervention, including a synthesis of existing principles of generalization and examples of how these can be embedded in approaches to aphasia treatment in clinical and research settings. Method: Three articles collectively listing 20 principles of generalization formed the foundation for this tutorial. The seminal work of Stokes and Baer (1977) focused attention on generalization in behavioral change following treatment. Two aphasia-specific resources identified principles of generalization in relation to aphasia treatment (Coppens & Patterson, 2018; Thompson, 1989). A selective literature review was conducted to identify evidence-based examples of each of these 20 principles from the extant literature. Results: Five principles of generalization were synthesized from the original list of 20. Each principle was supported by studies drawn from the aphasia treatment literature to exemplify its application. Conclusions: Generalization is an essential aspect of meaningful aphasia intervention. Successful generalization requires the same dedication to strategic planning and outcome measurement as the direct training aspect of intervention. Although not all people with aphasia are likely to benefit equally from each of the principles reviewed herein, our synthesis provides information to consider for maximizing generalization of aphasia treatment outcomes. Supplemental Material: https://doi.org/10.23641/asha.24714399
Keywords: dept.cmd; peer-reviewed